Extra-respiratory comorbidities and transplantation in the French cystic fibrosis registry. (3rd August 2019) - Mainbourg, Sabine; Durieu, Isabelle; Dehillotte, Clémence; Reynaud, Quitterie
ABSTRACT: Background : To better understand the potential role of lung transplantation (LT) in accelerating or slowing down extrarespiratory cystic fibrosis (CF) complications, we compare the respective prevalence of extrapulmonary CF comorbidities in transplanted and nontransplanted adult CF patients. Methods : About 20% of the adult CF patients included in the French CF registry have undergone transplantation. We analyzed all adults included in the French CF registry in 2014 and compared them according to their transplant status, irrespective of the year of transplantation, to describe the prevalence of CF-related diabetes (CFRD), end-stage renal disease and osteoporosis (Chi-squared and Fisher's exact tests). Results : A total of 3339 adult CF patients were included in the French CF Registry and 673 (20.2%) were transplanted. Prevalence of CFRD was significantly higher in transplanted patients compared to nontransplanted patients irrespective of the age group; the prevalence of end-stage renal disease and osteoporosis was also significantly higher in transplanted patients. Conclusion : These results demonstrate the high prevalence of extrapulmonary comorbidities in transplanted CF adult patients particularly CFRD. We highlight the need for specific surveillance and prevention for transplanted CF patients who were already treated for extra espiratory comorbidities before lung transplantation, due to the potential aggravation of their comorbidities after transplantation.